Therapeutic potential and sustainable bioprocessing of Enterocin CC2: a probiotic-derived antimicrobial targeting Streptococcus mutans in oral health - Ng, Zhang Jin; Gan, Chee Yuen; Abu Zarin, Mazni; Lee, Chee Keong; Lan, John Chi Wei; Ng, Hui Suan; Tan, Joo Shun (Springer, 2025)
The growing threat of antimicrobial resistance in oral pathogens necessitates safe and sustainable alternatives to conventional therapies. Enterocin CC2, a novel bacteriocin from Enterococcus faecium CC2, was purified using an optimized polyethylene glycol (PEG)–citrate aqueous two-phase system (ATPS). The process achieved a purification factor of 4.73 and recovery yield of 73.33%, which improved to 5.13 and 84.61% with the addition of 4% NaCl. SDS-PAGE revealed a molecular size of ~ 5.5–6 kDa, and identity confirmation was obtained via HPLC and LC–MS. Enterocin CC2 displayed potent antimicrobial activity against Streptococcus mutans with MIC and MBC values of 0.50 and 1.00 mg/mL, respectively, and demonstrated faster bactericidal action than 0.2% chlorhexidine. ISO 10993–5 cytotoxicity testing confirmed its safety on 3T3-L1 cells at concentrations ≤ 1 mg/mL. These findings highlight enterocin CC2 as a promising candidate for oral health applications and establish PEG–citrate ATPS as a scalable, eco-friendly platform for bacteriocin purification.